APAKAH KEPERCAYAAN BERPERAN PENTING DALAM HUBUNGAN ANTARA FREKUENSI KOMUNIKASI MANAJER PENJUALAN-TENAGA PENJUALAN DAN JOB OUTCOMES? - Setyanto, Refius Pradipta (Performance, 2007)
This research examines structural model describing the relations among sales manager-salesperson communication frequency, salesperson trust on sales manager, task performance, and salesperson job satisfaction in the industries of insurance and multifinance.The results of empirical data analysis show that communication frequency directly and positively influences salesperson performance. Moreover, it is proved that communication frequency has a positive relation with trust. The next finding shows that salesperson trust on manager indicates a positive influence on job satisfaction, however there is no significant relationship with task performance. Finally, there is significant relationship between communication frequency and job satisfaction. In summary, of the five hypotheses, three hypotheses are supported.